Response of yield and yield components of six genotypes of Pinto beans (Phaseolus vulgaris L.) inoculation with Rhizobium phaseoli - Hadi khavari; Ghodratolah Shakarami (پژوهش‌های حبوبات ایران)

(untitled)
Introduction Increasing the production of crops to meet the food needs of a growing population of the world is a great necessity. Intensive farming is an agricultural system that uses more than necessary and unbalanced inputs (fertilizers and pesticides), causing major of pressure on the environment. Today, in conventional farming systems, due to the limited amount of agricultural land, as well as the growing need for crops produced in indigenous agriculture, they have led to unbalanced consumption without the management of chemical fertilizers in the production of these products. The use of chemical fertilizer: nitrogen (N), phosphate (P2O5), potassium (K2O) in 2014-year ad around the world to 85.5, 32.2 and 20.4 (Kg of nutrients per ha) respectively. In comparison with year 2000 (Within 14 years), 64.9, 25.9 and 18.2 (Kg of nutrients per ha) respectively: 31.7, 28.1 and 12 percent it has increased. This undesirable agricultural management can change species composition or reduce biodiversity in farmland, and thus affect their natural capabilities in terms of crop production. On the other hand, increasing the health and security of food products produced in agricultural systems to maintain the dynamism of soil and water resources in these canopy systems is important on the basis of ecological principles. On the other hand, unbalanced consumption without management of chemical inputs has led to instability in agricultural ecosystems and the irreparable economic and environmental consequences of their consumption in agriculture are known throughout the world.